Differential Activation of Signaling Pathways by Low‐Osmolar and Iso‐Osmolar Radiocontrast Agents in Human Renal Tubular Cells. Issue 2 (February 2014) - Andreucci, Michele; Faga, Teresa; Russo, Domenico; Bertucci, Bernardo; Tamburrini, Oscar; Pisani, Antonio; Sabbatini, Massimo; Fuiano, Giorgio; Michael, Ashour
ABSTRACT Radiocontrast media (RCM)‐induced nephrotoxicity (CIN) is a major clinical problem accounting for 12% of all hospital‐acquired cases of acute kidney injury (AKI). The pathophysiology of AKI due to RCM is not well understood, but direct toxic effects on renal cells have been postulated as contributing to CIN. It is believed that iso‐osmolar RCM (IOCM) are less nephrotoxic than low‐osmolar RCM (LOCM) but clinical data have been controversial. We have investigated the intracellular signaling pathways that may be affected by the LOCM iomeprol (IOM) and the IOCM iodixanol (IOD). Both IOM and IOD caused a dramatic decrease in phosphorylation of the kinase Akt at Ser473 and Thr308 in human renal tubular (HK‐2) cells, with IOM having a greater effect; IOM also caused a greater decrease in cell viability. IOM also had a greater effect on phosphorylation of p38 MAP kinases, JNKs, and NF‐kB (Ser276), and caused a marked decrease in the phosphorylation of forkhead box O3a (FOXO3a) and signal transducer and activator of transcription 3 (STAT3). However, IOD caused a greater decrease in the phosphorylation of mTOR (Ser2448) and phospho‐ERK 1/2 while both RCM caused a similar decrease in the phosphorylation of phospho‐p70S6 kinase (Ser371). In vivo studies showed that both IOM and IOD caused a significant decrease in both pAkt (Ser473) and pERK 1/2 in rat kidneys. Our study gives an insight into the possible mechanism of toxicity of RCM via their action on intracellular signaling pathways and may help in developing pharmacological interventions for their side‐effects. J. Cell. Biochem. 115: 281–289, 2014. © 2013 Wiley Periodicals, Inc.